Analisis Available Time pada Mesin A di PT. XYZ - Ivan Santosa; Felecia Felecia (Jurnal Titra, 2017)
PT. XYZ is a manufacture company which specializes in producing of car tires, motorcycle tires, truck tires, bus tires, etc. The purpose of this research is to determine the production capacity of machine A and knowing the right solution to maximize the capacity of machine A. Early quality review shows no definite capacity in the production process on a daily basis. Determination of capacity is done by taking data every production process by using stopwatch and conducted a series of data testing. The actual condition of initial production in march was 136 tires/day. The calculation of production capacity was 167 tires / day in March. The analysis of time cycle improvement is done using time motion study method, Man-Machine Chart map, and body ply material improvement on machine A. The result after actual implementation in April was 151 tires / day with capacity of 182 tires/day. The result of analysis shows that the production capacity is known and there is an increase of production capacity by 10% on machine A in PT.XYZ. The factor that makes no chances of catching up is because the percentage of downtime is too big and does not match the target.